Research Planning and Organization in Sweden. Fact Sheets on Sweden - Swedish Inst., Stockholm; Swedish Inst., Stockholm ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Swedish research policy and organization, research areas, university research institutes, and international research and development (R&D) cooperation are discussed. Swedish research policy may be characterized as sectorized, decentralized, and pluralistic. The governmental bodies responsible for research direction include the Ministry of Education and research councils. One research area of special interest is research on environmental conservation and pollution abatement. Technical R&D has been assigned a high priority. Government funds are channeled to collective research (i.e., research programs that are jointly financed by private enterprise and the government). The universities are used as much as possible for research commissioned by the official sectoral bodies, and to some extent for research under contract to the business community. In addition, a number of independent, state-run research institutes exist. In the Swedish research system, the academies have an independent status in their traditional role as promotors of research and science in different disciplines. Sweden is involved in international teamwork for coordinated research programs. (SW)
Availability: Swedish Institute, Box 7434, S-103 91 Stockholm, Sweden.
ERIC Note: Document contains small print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cooperative Programs; Foreign Countries; Government School Relationship; Higher Education; Public Policy; Research and Development Centers; Research Projects; Universities; Sweden; Research Universities; Reports, Descriptive